PENINGKATAN PRODUKTIVITAS TERNAK SAPI MELALUI PENYULUHAN DAN PENANGANAN REPRODUKSI DI NEGERI LIANG KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Souhoka, Demianus F.; Siwa, Isak P.; Labetubun, Jusak; Wattimena, Jeffrie; Manurung, Ropanti Uli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
This activity focuses on increasing the productivity of cattle through counseling and reproductive handling in Negeri Liang, Salahutu District, Central Maluku Regency. Negeri Liang has great agricultural and livestock potential. Among them in the livestock aspect, cattle reproduction has an important role in the economic development of the local community. However, constraints related to reproductive management, reproductive diseases and lack of care are the main obstacles for farmers in improving the productivity and welfare of their livestock. Limited access to information and resources as well as low understanding of effective reproductive management practices have led to a decline in cattle productivity in Negeri Liang. The implementation method included participatory counseling using visual media for 30 farmers, reproductive examination of 25 female cattle, and direct treatment of reproductive disorders. The results showed an 85% increase in farmers' understanding based on pretest and posttest evaluations. Additionally, 60% of treated cows showed estrus signs within two weeks after treatment. In conclusion, this PKM activity successfully enhanced reproductive literacy, provided direct technical solutions for reproductive cases, and produced educational modules that can be sustainably used by the farmers.